TVRI South Sulawesi Broadcasting Adaptation Strategy as a Public Broadcasting Institution in the Digitalization Era - Sariyani Sariyani; Mujahid Yunus; Alem Febri Sonni (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This research aims to find out the adaptation strategy of South Sulawesi TVRI broadcasting as a public broadcasting institution in the digitalization era, supporting and inhibiting factors of South Sulawesi TVRI broadcasting adaptation strategy as a public broadcasting institution in the digitalization era. This type of research is classified as qualitative research. Data collection techniques are observation, interview, and documentation. The data was then verified, processed and analyzed based on qualitative analysis. The results showed that the implementation of TVRI South Sulawesi's broadcasting adaptation strategy has been carried out by procuring digital infrastructure and technology, conducting training to improve human resources and keep up with the times, conducting content research according to public needs, forming a new unit called New Media Content (KMB) where the unit is specifically to see the development of digital media and implementing a digital multi-platform distribution strategy. Supporting factors in TVRI South Sulawesi's broadcasting adaptation strategy are technology and infrastructure, human resources, government regulations, programs aired and collaboration. While the inhibiting factors are viewers and limited funds for production due to budget efficiency.